Central bank digital currencies a potential response to the financial inclusion challenges of the Pacific. - Didenko,Anton N.; Buckley, Ross P. (Asian Development Bank, 2021)
It notes that well designed and implemented CBDCs could help expand financial inclusion and reduce the high cost of remittances. The authors recommend that Pacific island countries lay the groundwork for CBDCs by building specific knowledge and expertise within central banks.